Tree-crop interactions : agroforestry in a changing climate - Ong, C. K.,; Black, Colin R., 1948-; Wilson, Julia, 1952- (CABI, 2015)
This second edition, which includes 12 chapters, provides an important update on tree-crop interactions over the last two decades. Three new chapters have been added to describe the new advances in the relationship between climate change adaptation, rural development and how trees and agroforestry will contribute to a likely reduction in vulnerability to climate change in developing countries. Finally, a synthesis that focuses on the challenges of ongoing climatic change for tropical agroforestry systems is given.